2020
DOI: 10.1038/s42005-020-00479-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hermitian effects of the intrinsic signs in topologically ordered wavefunctions

Abstract: Negative signs in many-body wavefunctions play an important role in quantum mechanics because interference relies on cancellation between amplitudes of opposite signs. The ground-state wavefunction of double semion model contains negative signs that cannot be removed by any local transformation. Here we study the quantum effects of these intrinsic negative signs. By proposing a generic double semion wavefunction in tensor network representation, we show that its norm can be mapped to the partition function of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…, {k/2}, where {a} means the integer part of number a. For example, Fibonacci model is in fact the subset of integer spin of su(2) 3 model, where we set g = 1 and deformation parameter q = e 2πi 5 . If we set g = 2, q = e 4πi 5 , what we actually get is Yang-Lee model, the non-unitarity comes from the possible negative sign of the function…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, {k/2}, where {a} means the integer part of number a. For example, Fibonacci model is in fact the subset of integer spin of su(2) 3 model, where we set g = 1 and deformation parameter q = e 2πi 5 . If we set g = 2, q = e 4πi 5 , what we actually get is Yang-Lee model, the non-unitarity comes from the possible negative sign of the function…”
Section: Discussionmentioning
confidence: 99%
“…The input data is that contained in a unitary fusion category -the unitary condition ensures that the Hamiltonian of the model is Hermitian. It is thus a curious question whether there are new topological orders if we relax the unitary condition [3][4][5]. Clearly, this is more than pure academic curiosity, since the existence of non-Hermitian topological orders would open the possibility to designing new classes of open systems to realize fault tolerant quantum computations.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the above crucial progress in the noninteracting case, it turned out that correlation effects enrich topological phenomena as is the case of Hermitian sysetms [63][64][65][66][67][68][69][70][71][72][73] . For instance, it was reported that correlations induce topological ordered states such as fractional quantum Hall states 63,66 and spin liquid states 64,65,67 . In addition, a previous work addressed classification of symmetry-protected topological phases with the nontrivial line-gap topology which have Hermitian counter parts 74 .…”
Section: Introductionmentioning
confidence: 99%
“…Here, the topological order is accompanied by the presence of certain group or Matrix Product Operator (MPO) symmetries in the entanglement degrees of freedom of the tensor, which can be used to parametrize the ground space manifold and anyonic excitations alike [7][8][9]. The description of topologically ordered systems as PEPS based on entanglement symmetries suggests a natural way to construct and study topological phase transitions within PEPS, by applying deformations to the physical degrees of freedom which drive the system to a different phase (such as a trivial product state) [10][11][12][13][14][15][16][17]. In this language, the entanglement symmetry in the tensor is preserved throughout the path, but at some point, it no longer manifests itself in topological order.…”
Section: Introductionmentioning
confidence: 99%